Nicolas Bouvier, Prométhée voyageur - Hugo Manuel Vaz (Carnets)
The opposition between nomads and sedentary people goes back to the dawn of time. In the West, the nomad is often feared, but in Asia, he has a noble aura, as discovered by Nicolas Bouvier, a writer-traveller of Swiss origin, who, in the 1950s, set off with Thierry Vernet to discover the Central Asia, others, himself and essential values. Their Asian wandering, a joyful journey but full of pitfalls and suffering, is characterized by slowness, learning about deprivation, the importance of encounters, sharing, meditation on the values of life. The journey will last almost two years and will be the subject of the book L'Usage du monde. Like Prometheus who stole the divine fire, the fire of knowledge, to give it to the human community, Nicolas Bouvier, by giving an account of his slow and happy wandering, gives us the gift of discoveries gleaned along the way, of hidden knowledge, of austere wisdom.